The biological meaning of anti-HBC positive result in blood donors: relation to HBV-DNA and to other serological markers - Luiz C. Arraes; Ricardo Ximenes; Jean-Marie Andrieu; Wei Lu; Silvana Barreto; Leila M.M.B. Pereira; Adauto Castelo (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
In order to assess the potential risk of anti-HBc-positive blood donors for post-transfusional hepatitis and to investigate whether other HBV serological markers are capable of identifying the presence of the virus, 1000 first-time blood donors were enrolled between June and July 1997. These donors were screened using routine Brazilian blood center tests (HIV 1 and 2, HTLV 1 and 2, Chagas disease, Syphilis, HCV, HBsAg, anti-HBc and ALT ). The 120 (12%) found to be anti-HBc-positive underwent further tests: HBe, anti-HBe, anti-HBs and HBV-DNA by PCR. Ten cases were HBsAg positive and all were HBV-DNA positive by PCR. Three HBsAg-negative donors were HBV-DNA-positive. Two HBV-DNA-positive donors were also anti-HBs-positive. All the HBV-positive donors had at least one HBV marker other than anti-HBc. Anti-HBc is an important cause of blood rejection. Testing for HBsAg alone is not fully protective and anti-HBc remains necessary as a screening test. The presence of anti-HBs is not always indicative of absence of the virus. The addition of other HBV serological markers could represent an alternative in predicting the presence of the virus when compared with PCR. It is recommended that other studies should be carried out to confirm this finding.